2006
DOI: 10.1002/adfm.200500748
|View full text |Cite
|
Sign up to set email alerts
|

Parameters Influencing Charge Separation in Solid‐State Dye‐Sensitized Solar Cells Using Novel Hole Conductors

Abstract: Solid‐state dye‐sensitized solar cells employing a solid organic hole‐transport material (HTM) are currently under intensive investigation, since they offer a number of practical advantages over liquid‐electrolyte junction devices. Of particular importance to the design of such devices is the control of interfacial charge transfer. In this paper, the factors that determine the yield of hole transfer at the dye/HTM interface and its correlation with solid‐state‐cell performance are identified. To this end, a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
162
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(174 citation statements)
references
References 40 publications
8
162
0
4
Order By: Relevance
“…5,6,7,8,9 Some of these studies have shown that, under optimized conditions and for different dyes and thickness of the TiO2 layer, the dye regeneration yield of the device ranges between 0.9 and 1. This result suggests that either almost complete coverage of the dyed surface is achievable or transfer of holes between the dye molecules enables improved charge collection from dyes that are uncovered by the HTM.…”
Section: Introductionmentioning
confidence: 99%
“…5,6,7,8,9 Some of these studies have shown that, under optimized conditions and for different dyes and thickness of the TiO2 layer, the dye regeneration yield of the device ranges between 0.9 and 1. This result suggests that either almost complete coverage of the dyed surface is achievable or transfer of holes between the dye molecules enables improved charge collection from dyes that are uncovered by the HTM.…”
Section: Introductionmentioning
confidence: 99%
“…postulated from their study of different HTMs that the PFF may strongly impact the hole injection effi ciency (defi ned as the fraction of photogenerated holes that are successfully injected from dye cations to spiro-OMeTAD). [ 16 ] In a previous study, we estimated that approximately 49% PFF is required to provide a monolayer of dye coverage with spiro-OMeTAD, assuming 20 nm spherical TiO 2 pores and conformal coating of spiro-OMeTAD on adsorbed Z907. [ 13 ] Below this sub-monolayer threshold, a signifi cant fraction of dye molecules are not in contact with spiro-OMeTAD.…”
Section: The Effect Of Hole Transport Materials Pore Filling On Photovmentioning
confidence: 99%
“…12 The underperformance of ss-DSC is thought to be associated with three main challenges: (i) limited pore-filling of the mesoporous TiO 2 with the HTM to ensure the optimum composition of the photo-active layer, [13][14][15][16] (ii) panchromatic absorption of light, which is currently limited by the maximal film thickness of well-performing ss-DSCs, 17 and (iii) efficient charge generation and transport from the excited dye to maximize the current output from the sunlight. [18][19][20][21][22][23][24][25] While issues with efficient charge generation have been extensively addressed (though not resolved) in earlier work, [18][19][20][21][22][23][24] the related challenges of effective pore-filling and sufficient panchromatic absorption remains open. The use of novel panchromatic absorbers may extend the absorption range from currently 425-650 nm to 425-940 nm, with a potential gain of 60% extra in short-circuit current and thus a 25% increase in power conversion efficiency despite the accompanied loss in voltage due to the reduced bandgap of the absorber.…”
mentioning
confidence: 99%